Melatonin and diet-induced metabolic syndrome in rats. Impact on the hypophysial-testicular axis - Scacchi Bernasconi, Pablo A. (2013)
Fil: Scacchi Bernasconi, Pablo A. Pontificia Universidad Católica Argentina. Facultad de Ciencias Médicas. Departamento de Docencia e Investigación; Argentina